Suitability of the Amazonas region for beekeeping and its future distribution under climate change scenarios - Gómez Fernández, Darwin; García, Ligia; Silva López, Jhonsy O.; Veneros Guevara, Jaris; Arellanos Carrión, Erick; Salas Lopez, Rolando; Goñas Goñas, Malluri; Atalaya Marin, Nilton; Oliva Cruz, Manuel; Rojas Briceño, Nilton B. (Elsevier, 2025)
Beekeeping plays an important role in global food production and the conservation of wild species. However, determining territorial suitability and future distribution under climate change scenarios is a relatively under-studied area in Peru. This study assessed the beekeeping suitability of the Amazonas region and its variation under climate change scenarios in two projected periods (2041-2060 and 2081-2100), according to Shared Socioeconomic Pathways (SSP). The methodological framework integrated the Analytical Hierarchy Process (AHP) with Geographic Information Systems (GIS), and the Hadley Centre Global Earth Model - Global Coupled configuration 3.1 (HadGEM3-GC31-LL) was used for future climate analysis. The beekeeping suitability of the region was determined based on eleven criteria: four climatic, three topographic, and four environmental. The results indicate that beekeeping suitability is distributed as follows: 3.4% (1417.90 km²) with 'High' suitability, 79.2% (33,318.61 km²) with 'Moderate' suitability, 17.2% (7230.26 km²) with 'Marginal' suitability, and 0.2% (83.64 km²) as 'Not suitable'. Moreover, the average temperature across the region is projected to increase by approximately 3 °C under the SSP2-4.5 scenario and between 6 °C and 8 °C under the SSP5-8.5 scenario during the projected periods. Precipitation will decrease in the northern part of the region, while the southwestern part will experience an increase. In the highly suitable beekeeping area, a temperature increases up to 10.8 °C is expected, with frequent variations around 3 °C to 8 °C, affecting more than 500 km². Additionally, a reduction in precipitation up to 311 mm/year is projected, with predominant variations ranging from -49.5 to 32.8 mm/year over approximately 600 km². Therefore, it is suggested to implement strategies to mitigate these upcoming challenges, particularly if the modeled economic development under the SSPs continues. This study modeled and mapped areas with present conditions suitable for beekeeping and future climate behavior. The modeling aims to guide beekeepers and local authorities in developing sustainable practices and implementing preventive measures to address future climatic challenges.